Invasive and non-invasive group A β-haemolytic streptococcal infections in patients attending public sector facilities in South Africa: 2003–2015. Issue 1 (2nd January 2018) - Barth, Dylan; M Mayosi, Bongani; Badri, Motasim; Whitelaw, Andrew; E Engel, Mark
Abstract: Background: The burden of disease caused by group A streptococcus (GAS) in Africa is largely unknown. The aim of this study was to determine the incidence of invasive ( i GAS) and non-invasive GAS (non- i GAS) infections in patients attending the public health sector of South Africa. Methods: i GAS and non- i GAS infection was defined as GAS isolated in culture from sterile and non-sterile sites respectively. Using annual census data, we calculated incidence rates (IR) of i GAS and non- i GAS infection by reviewing cases from the National Health Laboratory Service (NHLS) database derived from the 9 provinces of South Africa between 2003 and 2015. Results: About 50% of the samples were collected in the Eastern Cape province which had data for all the years under observation; missing data from the other eight provinces precluded analysis of annual incidence. A multi-modal distribution of 5 256 GAS cases was observed in the Eastern Cape province. i GAS cases ( n  = 428) showed an annual mean IR of 0.48 (Range: 0.15–1.12) cases per 10 5 per year (py) with a marginal decrease from 2003 to 2015 (Rate Difference (RD), 0.23/10 5 py; 95% CI: 0.02–0.44/10 5 py). The mean annual IR for non- i GAS infection ( n  = 4828) was 5.48 (Range: 0.19–11.55) cases/10 5 py; IR showed a decrease (RD, 11.36/10 5 py; 95% CI: 10.53–12.19/10 5 py). The Mann-Kendall test and the Theil-Sen estimator showed a decreasing trend in the incidence of non- i GAS infection ( p  = 0.002) over the study period. Conclusions: The incidence of non- i GAS infection in the Eastern Cape province of South Africa declined from 2003 to 2015. The trends from the Eastern Cape and incomplete data from other provinces indicate the need for a detailed prospective evaluation of GAS infection in South Africa to verify this trend and provide information for planning appropriate interventions.